2021
DOI: 10.1051/0004-6361/202039360
|View full text |Cite
|
Sign up to set email alerts
|

Fitting infrared ice spectra with genetic modelling algorithms

Abstract: Context. A variety of laboratory ice spectra simulating different chemical environments, ice morphologies, and thermal and energetic processing are needed in order to provide an accurate interpretation of the infrared spectra of protostars. To decipher the combination of laboratory data that best fits the observations, an automated, statistics-based computational approach is necessary. Aims. We aim to introduce a new approach, based on evolutionary algorithms, to searching for molecules in ice mantles via spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Many different COMs have been identified in the gas phase through radio and submillimeter surveys (e.g., Blake et al 1987;Jørgensen et al 2012;McGuire et al 2016;Belloche et al 2020;van Gelder et al 2020;McGuire 2021;Jørgensen et al 2020;Nazari et al 2021;Rivilla et al 2021;Brunken et al 2022), but astronomical observations have not been able to unambiguously identify frozen COMs larger than CH 3 OH due to low spectral resolution or sensitivity. Nevertheless, tentative detections of CH 3 CHO (acetaldehyde) and CH 3 CH 2 OH (ethanol) ice have been reported in the literature (Schutte et al 1999;Öberg et al 2011;Terwisscha van Scheltinga et al 2018;Rocha & Pilling 2015;Rocha et al 2021). Consistently with these tentative detections, several laboratory experiments have shown that such molecules can be formed in ices.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Many different COMs have been identified in the gas phase through radio and submillimeter surveys (e.g., Blake et al 1987;Jørgensen et al 2012;McGuire et al 2016;Belloche et al 2020;van Gelder et al 2020;McGuire 2021;Jørgensen et al 2020;Nazari et al 2021;Rivilla et al 2021;Brunken et al 2022), but astronomical observations have not been able to unambiguously identify frozen COMs larger than CH 3 OH due to low spectral resolution or sensitivity. Nevertheless, tentative detections of CH 3 CHO (acetaldehyde) and CH 3 CH 2 OH (ethanol) ice have been reported in the literature (Schutte et al 1999;Öberg et al 2011;Terwisscha van Scheltinga et al 2018;Rocha & Pilling 2015;Rocha et al 2021). Consistently with these tentative detections, several laboratory experiments have shown that such molecules can be formed in ices.…”
Section: Introductionmentioning
confidence: 55%
“…It should be noted that such synthetic spectra allow the reproduction of observed data but do not necessarily provide a unique solution. Other public codes, such as the ENIIGMA fitting tool (Rocha et al 2021) have the goal of quantifying the degeneracy of those fits when a large dataset of inputs is taken into account.…”
Section: Synthetic Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…ENIIGMA global fitting and local fits: We used the ENIIGMA fitting tool 49,50 to simultaneously fit multiple features across the NIRSpec and MIRI/LRS range by scaling laboratory ice spectra to match the optical depths in Figure 1. A full list with data used in this paper is shown in Table 3.…”
Section: Data Qualitymentioning
confidence: 99%
“…The ENIIGMA global fitting tool 49 is publicly available on GitHub at the following URL: https://github.com/willastro/EN fitting-tool…”
Section: Data Availabilitymentioning
confidence: 99%